Development of the evaluation function of internal audit - N. V. Timofeeva (Путеводитель предпринимателя, 2020)
The article defines and describes the stages of the transformation of its functions in the evaluation of internal audit, based on a retrospective evaluation of the development of the stages and methodology of internal audit in the credit organizations. The article describes the relationship between the targets of internal audit, functions and its methodology.